Fundamentos para uma distinção entre liberdade de expressão e Fake News – Liefare - a partir da crítica hermenêutica do Direito - Oliveira, Luiz Antonio da Silva (Universidade do Vale do Rio dos Sinos, 2025)
The thesis investigates the foundations and limits of the right to freedom of expression in light of the Fake News phenomenon within contemporary constitutional democracies. It is based on the premise that freedom of expression is an indispensable condition for the consolidation of the Democratic Rule of Law, especially during electoral periods when the formation of popular will depends on truthful and transparent information. The study, grounded in the Hermeneutic Critique of Law – a theoretical framework developed by Lenio Streck –, seeks to establish criteria capable of distinguishing freedom of expression (as a principle-based argument) from Fake News (as a predatory political argument, or Liefare). Methodologically, it adopts hermeneutic phenomenology, drawing on Heidegger and Gadamer, through documentary and bibliographical research. The analysis focuses on the 2018 and 2022 Brazilian elections, in which Fake News proved decisive in manipulating public opinion. It concludes that freedom of expression and Fake News are essentially incompatible phenomena, making it necessary to establish legal criteria that preserve freedom without allowing its capture by disinformation practices.

La tesis investiga los fundamentos y límites del derecho a la libertad de expresión frente al fenómeno de las Fake News en el contexto de las democracias constitucionales contemporáneas. Se parte del supuesto de que la libertad de expresión constituye una condición indispensable para la consolidación del Estado Democrático de Derecho, especialmente durante los períodos electorales, en los cuales la formación de la voluntad popular depende de información veraz y transparente. El estudio, a la luz de la Crítica Hermenéutica del Derecho – marco teórico desarrollado por Lenio Streck –, busca establecer criterios que permitan distinguir la libertad de expresión (como argumento de principio) de las Fake News (como argumento de política depredadora, el Liefare). Metodológicamente, se adopta la fenomenología hermenéutica, basada en Heidegger y Gadamer, mediante investigación documental y bibliográfica. El análisis se centra en las elecciones de 2018 y 2022, en las cuales las Fake News demostraron ser decisivas en la manipulación de la opinión pública. Se concluye que la libertad de expresión y las Fake News son fenómenos esencialmente incompatibles, siendo necesario establecer criterios jurídicos que preserven la libertad sin permitir su captura por prácticas de desinformación.
Keywords: Liberdade de expressão; Fake news; Democracia; Crítica Hermenêutica do Direito; Liefare; Freedom of expression; Democracy; Hermeneutic Critique of Law; Libertad de expresión; Crítica Hermenéutica del Derecho; ACCNPQ::Ciências Sociais Aplicadas::Direito